Philosophical Beliefs of Counselor Trainee - Ryan, Charles W.; Butzow, John W. (Canadian Journal of Counselling and Psychotherapy, 2012)
In this study, comparisons of measured philosophical beliefs, philosophical positions related in an interview, and counseling behavior were made for 22 counselor trainees at the University of Maine at Orono. The measurement of philosophical beliefs was made by using the Ames Philosophical Beliefs Inventory. High agreement was found between these three methods of evaluating philosophical beliefs. Many trainees were un- able to explain or understand their philosophical belief or show its implica- tions in counseling behavior. Suggestions for the improvement of counselor education, based on the findings, are listed.